Stephen H. Sherrill report and note - Sherrill, Stephen H. (Stephen Huntting), 1893-1956.
Note (1918 December 9) written by Sherrill to the burgermeister of Remagen, Germany, concerning the display of the American flag to attract U.S. Army soldiers to a tavern and a later report concerning the incident.
Army officer.
In part, positive and negative photocopies.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army -- History -- World War, 1914-1918.; Flags -- United States; Germany -- History -- 1918-1933.; Remagen (Germany) -- History; Army officers